2007
DOI: 10.1038/sj.emboj.7601714
|View full text |Cite
|
Sign up to set email alerts
|

Chk1 regulates the density of active replication origins during the vertebrate S phase

Abstract: The checkpoint kinase 1 (Chk1) preserves genome integrity when replication is performed on damaged templates. Recently, Chk1 has also been implicated in regulating different aspects of unperturbed S phase. Using mammalian and avian cells with compromised Chk1 activity, we show that an increase in active replicons compensates for inefficient DNA polymerisation. In the absence of damage, loss of Chk1 activity correlates with the frequent stalling and, possibly, collapse of active forks and activation of adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
240
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(269 citation statements)
references
References 27 publications
29
240
0
Order By: Relevance
“…3e). Furthermore, we did not observe modifications in the distribution of the classified replication figures 13 in curcumin-treated cells ( Supplementary Fig. S5), suggesting that the increased S-phase length might not be due to replicative stress, even though we measured a doubling of S-phase length.…”
Section: Resultsmentioning
confidence: 77%
“…3e). Furthermore, we did not observe modifications in the distribution of the classified replication figures 13 in curcumin-treated cells ( Supplementary Fig. S5), suggesting that the increased S-phase length might not be due to replicative stress, even though we measured a doubling of S-phase length.…”
Section: Resultsmentioning
confidence: 77%
“…Chk1, along with its upstream kinase ATR, constitutes an S-phase checkpoint that in unperturbed cells regulates the replication origin activation and contributes to S-phase progression. 36,37 Unprogrammed initiation of DNA synthesis in terminally differentiated neurons concomitant with the constitutive downregulation of Chk1 could thus contribute to aberrant replicative structures, fork collapse and ultimately cell death.…”
Section: Discussionmentioning
confidence: 99%
“…These include overexpression of translesion DNA polymerases (Pillaire et al 2007), the depletion of CHK1 (Maya-Mendoza et al 2007), BLM (Rao et al 2007), HR proteins (Daboussi et al 2008), and topoisomerase I (Tuduri et al 2009) and exposure to HU (Ge et al 2007;Ibarra et al 2008). Importantly, the latter studies also revealed that dormant origins are dispensable for normal growth but are essential for viability under replication stress (Ge et al 2007;Ibarra et al 2008).…”
Section: Dna Fiber Analyses Of Metazoan Replication Programsmentioning
confidence: 99%